LncRNA MIR99AHG enhances adipocyte differentiation by targeting miR-29b-3p to upregulate PPARγ - Zhang, Lin; Ma, Jinfang; Pan, Xiaohui; Zhang, Mei; Huang, Wei; Liu, Yanjun; Yang, Huawu; Cheng, Zhong; Zhang, Guixiang; Qie, Mingrong; Tong, Nanwei (Molecular and cellular endocrinology, 2022)
The aim is to identify new long noncoding RNAs (lncRNAs) involved in adipocyte differentiation. High-throughput RNA sequencing of 3T3-L1 preadipocytes was carried out before and after differentiation to identify the target lncRNAs and miRNAs. The effects of lncRNA, miRNA and the network mechanism on adipocyte differentiation were evaluated in vitro and in vivo. Visceral adipose tissue (VAT) was collected from Chinese subjects with obesity or a normal body mass index (BMI), and the levels of lncRNAs, adipogenic genes and miRNAs were measured. MIR99AHG, miR-29b-3p were selected as the target lncRNA and miRNA. Short hairpin RNA against MIR99AHG inhibited the differentiation of 3T3-L1 preadipocytes, reduced the expression of the peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT enhancer-binding protein alpha (C/EBPα) and fatty acid binding protein 4 (FABP4) genes, upregulated the expression of miR-29b-3p. Overexpression of MIR99AHG showed the opposite effects. Overexpression of miR-29b-3p inhibited the differentiation of 3T3-L1 preadipocytes and decreased the PPARγ level, while inhibition of miR-29b-3p showed the opposite effects. MIR99AHG and PPARγ competed for binding to miR-29b-3p. In mice with high-fat diet-induced obesity, MIR99AHG and miR-29b-3p mRNA level were increased and decreased, respectively. Tail vein injection of adeno-associated virus 9-MIR99AHG-RNA interference (AAV9-MIR99AHG-RNAi) reduced the body weight, epididymal fat mass, MIR99AHG level and increased the expression of miR-29b-3p. The expression levels of MIR99AHG, PPARγ, C/EBPα and FABP4 in human visceral adipose tissue were higher in the obese group than in the normal weight group. MIR99AHG enhances adipogenesis by regulating miR-29b-3p and PPARγ, providing a new target for therapeutic intervention in obesity. •MIR99AHG and miR-29b-3p are selected as the target lncRNA and miRNA during 3T3-L1 preadipocytes differentiation.•Inhibition of MIR99AHG prevents obesity in mice.•MIR99AHG sponges miR-29p-3p to promote PPARγ-mediated regulation of preadipocyte differentiation.